Bacterial profiling of colorectal cancer biopsies: a culture-based study in Indian patients - Kushwaha, Manish; Chaudhary, Shubham; Singh, Akhilesh Kumar; Makharia, Govind K.; Kumar, Anil (Frontiers in Cellular and Infection Microbiology, 2025)
Emerging research has highlighted the significant role of microorganisms in the initiation and progression of colorectal cancer (CRC). However, further investigation is required to elucidate the precise mechanisms by which the microbial community or specific bacteria contribute to carcinogenesis. The present work deals with the isolation and identification of bacteria from nine CRC biopsy samples and nine adjacent normal biopsy samples. Different media, such as brain heart infusion (BHI), anaerobic basal agar (ABA), and trypticase soy agar (TSA), and culture conditions have been manipulated to maximize the isolation of bacteria residing in biopsy samples. A total of 75 bacteria were isolated from the tumor and adjacent site. Enterococcus, Escherichia, Klebsiella, Shigella, Citrobacter, Morganella, and Veillonella have been found to be enriched in most of the tumor biopsies, while biopsies collected from adjacent tissues had Escherichia, Shigella, Enterococcus, and Streptococcus bacteria. A culture-based approach to assessing bacterial diversity offer advantages, enabling the study of individual bacteria to elucidate mechanisms of intestinal carcinogenesis. This approach may provide novel insights into pathology and potentially lead to new therapeutic modalities targeting the specific bacteria implicated in the inflammation and carcinogenesis of CRC.